Context effects in valuation, judgment and choice a neuroscientific approach - Hytönen, Kaisa (ERIM PhD Series in Research in Management, 2011)
"It is well known that our choices and judgments depend on the context. For instance, prior experiences can influence subsequent decisions. People tend to make riskier decisions if they have a chance to win back a previous loss or if they can gamble with previously won money. Another example of context is social environment. People often change their judgments to conform to observed group behavior. Since the reasons driving such context effects are less clear, this dissertation explores the mechanisms behind behavioral patterns with the help of a modern neuroscience technique, functional magnetic resonance imaging. The dissertation concentrates particularly on choice and judgment in risky and in social settings. It consists of three parts. The first part provides a primer on the methodology of neuroeconomics and a synthesis of the body of knowledge on the brain mechanisms of valuation and choice. The second part investigates risk behavior in sequential choice situations. The findings suggest that decision makers tend to take excessive risk after both wins and losses, due to increasing affective arousal and decreasing control. The third part of this dissertation focuses on the influence of social context on judgment. Results indicate that people automatically learn to behave as others do--being different from others is processed in the brain in a similar way to behavioral errors. This indicates the great power of relevant social groups in influencing our behavior. Overall, this dissertation highlights the reasons behind context dependency and demonstrates the power of modern neuroscientific methods for understanding economic behavior."--publisher.